THE The Realization of Lecturers’ Code-Switching in English Teaching and Learning Process At Dian Nuswantoro Univesity - Tyas, Dyah Ayu Enggaring; Rukmini, Dwi; Faridi, Abdurrachman (English Education Journal, 2021)
This study was focused on the analysis of code-switching occurred in the English teaching and learning process at non-English major class. This study examined the code-switching forms and functions of code-switching in the classroom. This study focuses on the analysis of code-switching occurred in the English teaching and learning process at non-English department class. This study examines the forms and functions of code-switching in the classroom at the lecturing process of English major as conduced at non-English department of Dian Nuswantoro university. Findings of the study showed that (1) the teaching learning process of non-English department class at Dian Nuswantoro university students employed various kinds of code-switching both by lecturers and the students with the dominant used was inter-sentential code-switching/full sentence code-switching. (2) there were various functions of code-switching utilized by the lecturer and students in the lecturing process, such as put an interjection in the middle of speech, to give emphasis toward certain topic, to repeat the speech, to give more description about certain topic, to talk about particular topic, to soften and straighten the request or command, to exclude others from the discussion, to express group identity, and to quote somebody’s utterances. Further studies hopefully can explore deeply about code-switching where lecturers teach English department students and uncover the lecturer and students’ perception on the occurrence of code-switching as the comparison to this current study.